Medieval Castles and Pre-modern Castle Towns Planned with Nature As The Heritages for Landscape Design Today -A Case Study of Nanbu Region in Tohoku- - Sugano, Keisuke; Okitsu, Ryutaro; Satoh, Shigeru (International Planning History Society Proceedings, 2016)
This research is to manifest the nature-symbiosis methods that distinguish the Nanbu castle towns built in the Edo Era from the castle towns elsewhere in Japan. Ever since the early 13th century onwards the Nanbu Clan had ruled Tohoku region till the end of Edo; their feudal lords respect the native mountain-worship, e.g., Iwakura (revering huge rocks as certain divinity’s beings); these17th century Nanbu castle towns – Morioka, Hachinohe and Tohno – were planned with visible mountain tops views and had Iwakura Rock as center of concentric circle on which the town installations were placed. The Nanbu Clan declined, and the framework of castle towns became the foundation for urban modernisation from 1800 onwards. Morioka Castle Town, the prominent among three, has been modernised as the capital of Iwate Prefecture today; its historical heritages enliven the town making by government and citizenry. This paper concerns itself with the relation between Nanbu castle towns and Nature, with that among town construction, micro-topology, Iwakura and Mountains worship, with that between street composition and the locations of temples, shrines and other installations. Analysing Morioka castle town through modern landscaping science, this research tries to discover the relation between planning and Nature, seeking to revive the vista of the Nanbu mountain-worship. First, through field investigation and reading of historical texts, the street axes extended to link up the mountain tops of Object Mountain as Yama-ate are verified; the religious tie between Nanbu Clan and Object Mountains is analysed. Second, historical texts help grasp the religious installations in Nanbu, analysing their locations, micro-topography, and castle installation by GIS. Third, verify the Yama-ate street axes and their relation with temples and shrines by GIS; measure the streets, parallel or perpendicular, to the Yama-ate main street; and analyse the relation between urban frame and the mountains. Forth, how are those mountain views required by Morioka City related to the Nanbu mountain worship? The analyses show that the historical planning corresponded to their environment; the street composition, including temples and shrines, did link up the Mountain, Iwakura objects and micro-topography. And, the medieval methods like vista are employed to revive the castle town cities today with four points below: 1) A Yama-ate Street provides us unobstructed view of the mountains worshiped; the Yama-ate highways that terminate at castle gate or temple entrance path must be verified. 2) The temples strongly tied to the Clan are located in the areas of slight elevation in Nanbu District. Also, several points nearby the castle gate are built with temples to worship the sacred mountains. 3) Morioka is distinctive, the main street axis terminates the excavated Iwakura; various castle gates are designed with same distance towards the Iwakura. 4) The Morioka landscaping policy today has a set of rules: e.g., the height of building is limited to keep the mountain views visible from the bridges or from the castle park; all the rules are made to preserve the views of mountains worshipped in the medieval.